Phase 2 trial of montelukast for prevention of pain in sickle cell disease - Field, Joshua J. (Blood Adv, 2020)
Cysteinyl leukotrienes (CysLTs) are lipid mediators of inflammation. In patients with sickle cell disease (SCD), levels of CysLTs are increased compared with controls and associated with a higher rate of hospitalization for pain. We tested the hypothesis that administration of the CysLT receptor antagonist montelukast would improve SCD-related comorbidities, including pain, in adolescents and adults with SCD. In a phase 2 randomized trial, we administered montelukast or placebo for 8 weeks. The primary outcome measure was a >30% reduction in soluble vascular cell adhesion molecule 1 (sVCAM), a marker of vascular injury. Secondary outcome measures were reduction in daily pain, improvement in pulmonary function, and improvement in microvascular blood flow, as measured by laser Doppler velocimetry. Forty-two participants with SCD were randomized to receive montelukast or placebo for 8 weeks. We found no difference between the montelukast and placebo groups with regard to the levels of sVCAM, reported pain, pulmonary function, or microvascular blood flow. Although montelukast is an effective treatment for asthma, we did not find benefit for SCD-related outcomes. This clinical trial was registered at www.clinicaltrials.gov as #NCT01960413.